PENGGUNAAN BERBAGAI JENIS DAN DOSIS BIOCHAR TERHADAP EMISI KARBON DIOKSIDA, NITRAT DAN MIKROORGANISME PADA TANAH - Zustika, Sri; Khusrizal; Akbar, Halim; Nasruddin (Jurnal Tanah dan Sumberdaya Lahan, 2025)
Soil serves as a medium for the absorption of greenhouse gases due to its organic carbon content; however, its capacity to absorb greenhouse gases has been declining. One of the contributors to carbon dioxide (CO2) emissions in agriculture is soil microorganism respiration, while high nitrogen (N) loss is attributed to its mobility. The application of biochar has the potential to reduce greenhouse gas emissions and improve soil quality. This study aimed to analyze the effects of different types and doses of biochar on reducing CO2 emissions, increasing nitrate levels, and enhancing microorganism populations. The research was conducted in the Soil Laboratory of Agroecotechnology, Malikussaleh University, using a completely randomized factorial design (CRD) with two treatment factors. Factor 1 was the type of biochar: (J1) rice husk biochar, (J2) giant bamboo biochar, and (J3) sweet corn cob biochar. Factor 2 was the biochar dosage: (D0) 0 tons ha⁻¹, (D1) 10 tons ha⁻¹, (D2) 20 tons ha⁻¹, (D3) 30 tons ha⁻¹, and (D4) 40 tons ha⁻¹. Parameters analyzed included CO2 emissions, soil nitrate levels, and microorganism populations. The results showed that rice husk biochar effectively reduced CO2 emissions from soil microorganism respiration to 4.08 kg CO2 ha⁻¹ hour⁻¹, increased soil nitrate levels to 8.14 ppm, and enhanced microorganism populations. The optimal biochar dosage was 30 tons ha⁻¹.